OPINION OF COLLEGE STUDENTS ABOUT COMPREHENSIVE LEARNING AND DIDACTIC INSTRUMENTATION IN THE CLASSROOM - Rodríguez, Reyna del Carmen Martínez; Corona, Lilia Benítez; Mora, Jorge Arturo Vásquez (Advances in Social Sciences Research Journal, 2014)
ABSTRACT: This paper reports the opinion of a group of engineering students from the Polytechnic University of Pachuca, Mexico about the comprehensive learning and didactic instrumentation in the humanities courses within the university as an opportunity area for analysis of real situations. It was used mixed methodology: in the first part a questionnaire was applied and, in the second part, the focus groups technique was used. For this research were considered contributions of Delors (7) Morin (19), and Torroela (23). The discoveries of this research revealed the importance of the contents of humanities courses and some other essential factors in the didactic instrumentation that impact comprehensive learning.